Radical Transformations towards the Synthesis of Quinoline: A Review. Issue 24 (16th November 2020) - Teja, Chitrala; Khan, Fazlur Rahman Nawaz
Abstract: Quinoline is considered one of the most ubiquitous heterocycles due to its engaging biological activities and synthetic utility over organic transformations. Over the past few decades, numerous reports have been documented in the synthesis of quinolines. The classical methods including, Skraup, Friedlander, Doebner‐von‐Miller, Conrad‐Limpach, Pfitzinger quinoline synthesis, and so forth, these are the well‐known methods to construct principal quinoline scaffold with several advantages and limitations. Recently, radical insertion or catalyzed reactions have emerged as a powerful and efficient tool to construct heterocycles with high atom efficiency and step economy. In this concern, this minireview mainly focused on the developments of Quinoline synthesis via radical reactions. In addition, a brief description of the preparation procedure, reactivity, and mechanisms is also included, where as possible. Respectively, the synthesis of quinolines is classified and summarized based on its reactivity, so it will help the researchers to grab the information in this exploration area, as Quinolines are promising pharmacophores. Abstract : In the past few years, radical reactions, including photoredox catalysis, transition metal‐based reactions, electrocatalysis, and so forth, have blossomed to construct heterocycles with many advantages compared with traditional methods. Quinoline is a nitrogen heterocycle with several biological applications as a potential drug candidate and a functional molecule in organic synthesis and other fields. In the present review, we discussed quinolines′ synthesis from radical reactions; a brief description of the preparation procedure, mechanism, and reactivity are enclosed.